Synthesis and characterisation of silica-polymer hybrid core-shell and hollow spheres for drug delivery applications - Lou, Xia; Schumacher, T.; Yang, H.; Ding, Ailin (Elsevier, 2011)
Silica-polymer hybrid core-shell structures and nano-hollow spheres with chemically immobilized hydrophobic, hydrophilic, and thermal sensitive functional groups on the surfaces were prepared through a simple synthetic approach for possible applications as a drug carrier. Both the core–shell and hollow structures of these particles were identified by a high resolution transmission electron microscopy (TEM). Sizes and their distributions of both the core-shell structures and the hollow spheres were investigated using a dynamic light scattering size analyzer and further confirmed by the atomic force microscopy (AFM). The method can easily be adapted for the fabrication of similar nano structures that contain biological macro-molecules for the delivery of biotherapeutics.